National and Transnational Challenges to the American Imaginary - Ciugureanu, Adina; Vlad, Eduard; Stanca, Nicoleta (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
The essays in this volume examine aspects of the ever-changing American imaginary over the last two centuries from the cultural perspectives of the present age, in which transnational approaches have vigorously challenged American exceptionalist narratives. It is a time in which uncertainties and reappraisals of group and national identity, both within the US and abroad, are part of the framework of a comprehensive field of research for scholars in American Studies, in the social sciences and the humanities alike. While situated in the current tumultuous century, the contributors of this volume focus on specific issues of the US defining and redefining itself from the mid-nineteenth century to the present.